RNA-dependent DNA polymerase activity of RNA tumor viruses. V. Rous sarcoma virus single-stranded RNA-DNA covalent hybrids in infected chicken embryo fibroblast cells. - Leis, J (1975)
RNA-DNA covalent hybrids containing viral RNA have been isolated from nuclear fractions of Rous sarcoma virus-infected chicken embryo fibroblast cells shortly after virus infection. The formation of covalent hybrid structures depends upon a functional reverse transcriptase in vivo, since its appearance in cells is temperature dependent when infected with Rous sarcoma virus mutant LA335, which contains a temperature-sensitive reverse transcriptase.